Challenges of reaching 90–90–90 in the Southern United States. Issue 6 (November 2019) - Colasanti, Jonathan A.; Armstrong, Wendy S.
Abstract : Purpose of review: More than half of new HIV diagnoses occur in the Southern United States where the epidemic disproportionately affects persons of color. Although other areas of the country are seeing dramatic declines in the number of new cases, the progress in the South lags behind. This review will examine the reasons for that disparity. Many are unique to the South. Recent findings: Despite advances in antiretroviral therapy for HIV, many in the South are not benefiting from these medications, at either a personal or public health level. The reasons are complex and include lack of access to healthcare, lower levels of funding than other areas of the country, stigma, structural racism, increased barriers due to social determinants of health, coexisting mental health disorders, substance use disorders and sexually transmitted diseases and insufficient workforce capacity to meet the needs of those living with HIV. Summary: These findings should underline the need for investment in the South for a holistic healthcare approach to persons living with HIV including supporting basic needs such as access to food, transportation and housing. Prioritization among politicians for policy and systems changes and approaches to decrease stigma and enhance education about HIV will be key.